PENDAMPINGAN KEWIRAUSAHAAN UNTUK MAHASISWA DAN PENGEMBANGAN DIGITAL MARKETING DI KECAMATAN CIAWI - Maesaroh, Imas; Ginting, Ginta; Pujiwati, Ami; Hidayah, Zainur; Sylvana, Andi; Lestari Pujiastuti, Sri; Nasoha, Mohamad; Sunarsih, Nenah; Irmawaty; Subekti, Rini; Ria Viana Praningtya, Elisabeth; Andriyansah, Andriyansah (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2024)
The urgency of this activity is to promote student products so that the products can be femilar in the market. The purpose of this community service activity is to provide assistance starting from management, packaging to marketing (promotion with digital marketing) applying economic analysis using BMC (Bussines Model Canvas) BMC is very helpful to speed up the process of analysing business strengths and weaknesses. Knowing the strengths and weaknesses, the analysis of needs and profits can be done quickly and effectively. The partner in this activity is "For You", a form of MSME business that offers various gifts. The method of implementation is Preparation for Determination of PkM locations, then the team conducts Introductions by coordinating and consulidating with Gift Shop partners "For You". Furthermore, conducting counselling and mentoring Production and marketing operations Implementation of production activities Business training on Social Media Gift Shop "For You" Participants who are active in this activity are 6 people The results of its implementation are able to use digital marketing technology to market their gift products using digital marketing using mass media, seen the number of visitors who see the products displayed by partners on their social media accounts